To determine the incidence of post-operative deep vein thrombosis in general surgical patients of Hospital Universiti Sains Malaysia - Tun, Myint; Shuaib, Ibrahim Lutfi; Muhamad, Mahayidin; Sain, Abdul Hamid Mat; Ressang, Anas Sjahroedin (2001)
Apparent rarity of post-operative DVT and pulmonary embolism in Asian patients was first reported since 1964. Very few literature and clinical studies were done for post-operative DVT in Asian population as well as in Malaysia.Compared to the Western hemisphere,low incidence 2.6% to 15.3% was reported from Japan, Hong Kong, Thailand, Singapore and Malaysian studies.Conflicting results of high incidence in orthopaedic patients was reported in two other Asian studies from Hong Kong and Malaysia.To find out the incidence of post-operative deep vein thrombosis (DVT) in our general surgical patients after major surgical procedures.To find out the subgroups of patients at special risk to post-operative DVT.To reviewthe policy of withholding routine DVT prophylaxis in Malaysian patients.